Exploring the Shariah-Compliant Hotel Market: Meeting the Needs of Muslim Travelers - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study explores the dynamics of guest preferences and satisfaction within the context of Sharia-compliant hospitality, using data from 445 verified reviews at The Sahira Hotel. Employing a descriptive-analytic methodology, the research utilizes visitor data extracted from Agoda’s review platform, focusing on room preferences, stay duration, and satisfaction ratings. The dataset was systematically filtered, cleaned, and categorized to ensure relevance and accuracy before conducting qualitative and quantitative analyses. Key findings reveal significant trends in visitor demographics and preferences. Families with young children and teenagers strongly preferred spacious accommodations, particularly the Family Deluxe Triple, accounting for over 35% of such bookings. In contrast, solo travelers, representing 20% of the dataset, favored functional and affordable options like the Deluxe Twin. Ratings analysis revealed the Deluxe Twin as the most highly rated room type, receiving over 40%